Randomized Phase II Trial of Parsatuzumab (Anti‐EGFL7) or Placebo in Combination with Carboplatin, Paclitaxel, and Bevacizumab for First‐Line Nonsquamous Non‐Small Cell Lung Cancer. (7th February 2018) - von Pawel, Joachim; Spigel, David R.; Ervin, Thomas; Losonczy, György; Barlesi, Fabrice; Juhász, Erzsébet; Anderson, Maria; McCall, Bruce; Wakshull, Eric; Hegde, Priti; Ye, Weilan; Chen, Daniel; et al.
Abstract : Lessons Learned : The lack of efficacy associated with anti‐EGFL7 combined with standard bevacizumab and chemotherapy in this phase II trial in non‐small cell lung carcinoma is consistent with the lack of benefit observed in colorectal carcinoma, highlighting the challenge of enhancing the efficacy of VEGF inhibition in unselected populations. Future efforts with agents like anti‐EGFL7 should be guided by advances in pharmacodynamic and predictive biomarker development for antiangiogenic agents. Background: Epidermal growth factor‐like domain 7 (EGFL7) is an extracellular matrix‐associated protein that is upregulated during angiogenesis and supports endothelial cell survival. This phase II trial evaluated the efficacy of the anti‐EGFL7 antibody, parsatuzumab, in combination with bevacizumab plus platinum‐based therapy for advanced or recurrent nonsquamous non‐small cell lung cancer (NS‐NSCLC). Methods: Patients ( n  = 104) were randomized to either placebo or parsatuzumab (600 mg) in combination with bevacizumab (15 mg/kg) and carboplatin/paclitaxel, administered on day 1 of each 21‐day cycle. Carboplatin and paclitaxel were administered for up to six cycles. Bevacizumab and parsatuzumab/placebo were administered for a maximum of 24 months. Results: The progression‐free survival (PFS) hazard ratio (HR) was 1.7 (95% confidence interval [CI], 1.0–2.8; p  = .047). The median PFS was 6.7 months for the parsatuzumab arm versus 8.1 months for the placebo arm. The hazard ratio for overall survival (OS) was 1.1 (95% CI, 0.5–2.2; p  = .847). The objective response rate (ORR) was 29% in the parsatuzumab arm and 56% in the placebo arm. Overall safety and tolerability were consistent with the established toxicity profile of bevacizumab. Conclusion: There was no evidence of efficacy for the addition of parsatuzumab to the combination of bevacizumab and chemotherapy for first‐line NS‐NSCLC.